Microanalytical Methods for Investigation of the Inflammatory Response - Guidry, Nate; Hallaq, Tom (Kansas State University, 2017)
A central focus of this research is the development of microfluidic devices for manipulating single cells and conducting measurements of cell chemical reactions using electrical and optical techniques. Microfluidic devices are ultrasmall plumbing networks of channels and valves which can precisely manage small volumes of liquids (one-millionth to a few billionths of a liter). Microfluidics thus enable the study of small systems such as living cells, and also the rapid collection of data. This project is a multidisciplinary/international collaboration between four research groups, each providing unique expertise and facilities.
Keywords: Culbertson, Christopher